PENGARUH LINGKUNGAN KERJA TERHADAP KUALITAS LAYANAN PADA PT. TIKI JALUR NUGRAHA EKAKURIR (JNE) CABANG MAKASSAR - Hasdiana S; Welli Ruswiananda (POINT: Jurnal Ekonomi dan Manajemen, 2019)
Effect of work environment on service quality at PT. TIKI Makassar Nugraha Ekakurir Line (JNE) Branch. This research is motivated by the importance of the work environment on service quality in the company, the purpose of this study is to determine the effect of the work environment on the quality of service at PT. TIKI Makassar Nugraha Ekakurir Line (JNE) Branch. The analytical method used to prove the hypothesis is the method of multiple regression analysis using SPSS and the number of respondents in this study were 57 people. The results of this study indicate that the physical work environment variable produces T-count (2.884) ≥ from the T-table value (1,673), the non-physical work environment variable produces T-count (0.588) ≤ from the T-table value (1,673). then the physical work environment affects the quality of service and the non-physical work environment does not affect the quality of service. The results of the F test indicate that F-count (7,065) F from the F-table (3.16), while the significance is 0.002 ≤ alpha at a significance level of 0.05, means the variable physical work environment, non-physical work environment variables and service quality variables.